2019
DOI: 10.1253/circj.cj-18-0807
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Importance of Drug-Drug Interaction Between Warfarin and Prednisolone and Its Potential Mechanism in Relation to the Niemann-Pick C1-Like 1-Mediated Pathway

Abstract: Background: Warfarin is an anticoagulant drug used to prevent thromboembolic disorders, but its pharmacological effect is affected by co-administered drugs. Therefore, careful management of warfarin-related drug-drug interactions (DDIs) is necessary for its safety and effectiveness. Recently, intestinal vitamin K1 absorption through the Niemann-Pick C1-like 1 (NPC1L1)-mediated pathway was found to affect the pharmacological effect of warfarin. This study aimed to identify high-frequency warfarin-related DDIs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Although warfarin was associated with piperacillin sodium and tazobactam sodium, imipenem and cilastatin sodium, the INR continued to increase 1 or 2 days after discontinuation of the two drugs, so the interaction between warfarin and the two drugs was not considered. INR increase has been reported when high-dose dexamethasone (>40 mg/day) and warfarin are concomitantly administered (Sellam et al, 2007), which may be due to the action of highdose synthetic glucocorticoids on Niemann-Pick C1-like 1 protein (Ito et al, 2019). However, the dose of dexamethasone in this patient was 5.0 mg once a day, which was too low to cause any DDIs.…”
Section: Subjectmentioning
confidence: 66%
“…Although warfarin was associated with piperacillin sodium and tazobactam sodium, imipenem and cilastatin sodium, the INR continued to increase 1 or 2 days after discontinuation of the two drugs, so the interaction between warfarin and the two drugs was not considered. INR increase has been reported when high-dose dexamethasone (>40 mg/day) and warfarin are concomitantly administered (Sellam et al, 2007), which may be due to the action of highdose synthetic glucocorticoids on Niemann-Pick C1-like 1 protein (Ito et al, 2019). However, the dose of dexamethasone in this patient was 5.0 mg once a day, which was too low to cause any DDIs.…”
Section: Subjectmentioning
confidence: 66%
“…13 The underlying mechanism for DDIs involves the action of high-dose synthetic glucocorticoids on Niemann-Pick C1like 1 protein. 14 However, the dose of dexamethasone in this patient was 6.6 mg, which was too low to cause any DDIs. Ciclesonide, an inhaled drug, has a low transferability (<1%) of active metabolites into the blood; therefore, it carries little to no risk of causing DDIs.…”
Section: A S E Summarymentioning
confidence: 78%
“…Another target, the glucocorticoid receptor, has a long history of pharmacological interaction with warfarin‐like molecules. Prednisolone and dexamethasone, potent glucocorticoid receptor agonists, are frequently associated with drug–drug interactions in patients treated with warfarin (Sellam et al 2007; Ito et al 2019). Moreover, it has been shown that warfarin induces vascular calcification (Jiang et al 2016), a process that is also facilitated by glucocorticoids, although the evidence points to a mechanism involving the mineralocorticoid receptor (Zhu et al 2016).…”
Section: Discussionmentioning
confidence: 99%